Analisis Postur Kerja Pada Pekerja Bagian Penyusunan Batu Bata di Stasiun Pengeringan dengan Metode Rapid Entire Body Assessement - Reza Fernando; Juarni Juarni (JURUTERA - Jurnal Umum Teknik Terapan, 2016)
Sei-sijenggi Village is a center for small brick-making industries in Perbaungan District, one of which is CV. Rahmad. The brick production process and material handling at CV. Rahmad is still manually, which relies on human power. In the brick making section at the drying station, workers often carry out brick-making activities by bending and twisting with a very high repetition frequency. In addition, work activities are dominated by standing work attitudes. The purpose of this study was to analyze the manual material handling (MMH) work posture at risk of Musculoskeletal Disorders (MSDs) using the Rapid Entire Body Aassessment (REBA) method and provide suggestions for improvement in work posture. Data collection is carried out by making observations directly taking the form of photos and videos of workers and evaluating work postures which include the attitude of the neck, back, legs, upper arms, forearms, wrists, workload weight, coupling factors or handrails using the Rapid Entire method Body Aassessment (REBA) with the help of ergofellow software. The results of this study show that there are workplaces at risk of complaints of Musculoskeletal Disorders (MSDs). From the research it can be concluded that the manual material handling (MMH) work posture for workers in the drying station preparation section must be repaired as soon as possible, so that they capable to conduct job evaluations, improve methods, systems and ways of working and the workers can work with high performance